'In-stock' fenestrated stent graft for the urgent repair of an abdominal aortic aneurysm. (20th May 2016) - Crawford, Sean A; Doyle, Matthew G; Tse, Leonard W; Roche-Nagle, Graham
Abstract : Endovascular aneurysm repair (EVAR) is a minimally invasive method for the treatment of abdominal aortic aneurysms; however, the implementation of this technique is often limited by the aortic pathology, especially in the urgent or emergent setting. An 82-year-old male with a 7.3 cm symptomatic juxtarenal aneurysm presented at our centre for assessment. He was diagnosed as a high-risk candidate for open repair and therefore, not suitable for a conventional EVAR. Fortunately, a custom two-vessel fenestrated stent graft, which was originally constructed for another patient, was available. This device was implanted with no complications and all branches remain unobstructed; clear of aneurysms at 1 year. We present the use of 'in-stock' fenestrated grafts as a potential option to be considered in the urgent or emergent repair of abdominal aortic aneurysms.